Exploring Student Interpretations of Moral Value in 'Slumdog Millionaire' - Sarair; Ayuna Netta; Raisha Elfianita (Proceeding of International Conference on Multidisciplinary Research, 2024)
This research delves into the portrayal of moral values in the renowned movie "Slumdog Millionaire" and their impact on the perceptions of fifth-semester students at Universitas Muhammadiyah Aceh. The study aimed to explore how cinematic representations of moral values could both inspire and educate students. Using a close-ended questionnaire with a Likert scale, data were collected from the students. The questionnaire was designed to assess students' perceptions regarding moral values depicted in the film, including belief in God, hard work, honesty and trustworthiness, perseverance, love and belonging, inspiration, positive thinking, patience, and self-confidence, with responses ranging from 1 (Strongly Disagree) to 5 (Strongly Agree). The research findings suggest that "Slumdog Millionaire" effectively conveys a spectrum of moral values, with belief in God, hard work, and honesty and trustworthiness being the most favorably perceived. Moreover, the film is widely regarded as inspirational, encouraging students to integrate these values into their lives. This study underscores the pivotal role of cinema in shaping students' perceptions of moral values, with "Slumdog Millionaire" emerging as a source of both inspiration and education, illustrating the potential of visual storytelling in imparting essential life lessons among fifth-semester students at Universitas Muhammadiyah Aceh.